HCI in business, government, and organizations. eCommerce and innovation : third International Conference, HCIBGO 2016, held as Part of HCI International 2016, Toronto, Canada, July 17-22, 2016, Proceedings /: eCommerce and innovation : third International Conference, HCIBGO 2016, held as Part of HCI International 2016, Toronto, Canada, July 17-22, 2016, Proceedings. Part II : (2016) - Unknown
No abstract available